Towards simulation-assisted performance monitoring of BIPV systems considering shading effects - Ghasempourabadi, Mohammadhossein; Sinapis, Kostas; Loonen, Roel C. G. M.; Valckenborg, Roland M. E.; Hensen, Jan L. M.; Folkerts, Wiep (2016 IEEE 43rd Photovoltaic Specialists Conference (PVSC), 2016)
Nowadays, the application of BIPV systems is growing very fast and among this type of technology, application of BIPV facade systems is becoming more common. A main question in this field is how we can ensure the intended performance of such systems considering different involved parameters over the system's life-time. To do so, we need to be able to predict normal behavior of BIPV systems in urban environments, considering the effect of shading from neighboring obstructions. This research investigates a combination of real-time shading simulation using Rhino and Grasshopper with BIPV performance monitoring to detect abnormal system operation. The application of this approach is demonstrated for a 12 m 2 vertical BIPV system in the SolarBEAT test facility in Eindhoven, the Netherlands. We have conducted an experiment to better understand the impact of different partial shading scenarios on the I-V curve of a vertical CIGS BIPV panel. The results show that the simulation-assisted approach, coupled with data visualization and a decision tree can be a powerful tool for guaranteeing robust BIPV system output.